Healthcare-Seeking Behavior among Tuberculosis Patients during the Covid-19 Pandemic in Padang City - Verra Widhi Astuti; Yessi Fadriyanti; Vier Nofrel (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2023)
Pulmonary TB has symptoms similar to covid-19 and also the easy way of spreading causes people to be reluctant to go to health services for fear of contracting or being diagnosed with covid-19. This has caused the number of case discoveries and the success of TB treatment to decrease. This study aims to determine the behavioral picture of health care search in pulmonary TB patients during the COVID-19 pandemic. This study is a cross-sectional study conducted on 100 pulmonary TB patients in Padang City aged more than 17 years, who are or have completed treatment at the Puskesmas Anak Air and Lubuk Buaya in January-June 2022 which were randomly selected. Data were collected through a modified questionnaire of healthcare-seeking behavior on pulmonary TB patients. The results showed that most respondents first visited public health services (51%), especially Puskesmas (52.9%), because they believed that pulmonary TB could be cured (62.7) and wanted to get health services from health workers (56.9%). However, there are still people who do not visit health services for the first time (49%) for fear of being diagnosed (55.1%) or contracting covid-19 (46.9%). For this reason, as nurses, we must continue to actively educate the public so that public knowledge about pulmonary TB and covid-19 increases and there is no negative perception of disease or anxiety in the community. Abstrak: TB paru mempunyai gejala yang mirip dengan covid-19 dan juga cara penyebaran yang mudah meyebabkan orang enggan ke pelayanan kesehatan karena takut tertular maupun terdiagnosis covid-19. Hal ini menyebabkan angka penemuan kasus dan keberhasilan pengobatan TB menurun. Untuk itu, penelitian ini bertujuan untuk mengetahui gambaran perilaku pencarian pelayanan kesehatan pada pasien TB paru selama pandemi covid-19. Penelitian ini merupakan studi cross-sectional yang dilakukan pada 100 pasien TB paru di Kota Padang berusia lebih dari 17 tahun, yang sedang atau telah menyelesaikan pengobatan di Puskesmas Anak Air dan Lubuk Buaya pada Januari-Juni 2022 yang dipilih secara acak. Data dikumpulkan melalui kuisioner perilaku pencarian pelayanan kesehatan pada pasien TB paru yang telah dimodifikasi. Hasil penelitian menunjukkan sebagian besar responden pertama kali mengunjungi  pelayanan kesehatan umum (51%), khususnya Puskesmas (52,9%), karena mereka percaya bahwa TB paru dapat disembuhkan (62,7) dan ingin mendapatkan layanan kesehatan dari tenaga kesehatan (56,9%). Namun, masih ada masyarakat yang tidak mengunjungi layanan kesehatan untuk pertama kalinya (49%) karena takut terdiagnosis (55,1%)  atau tertular covid-19 (46,9%).  Untuk itu, sebagai perawat, kita harus terus aktif memberikan edukasi kepada  masyarakat  agar  pengetahuan masyarakat tentang TB paru dan covid-19 meningkat serta tidak ada persepsi negatif terhadap penyakit atau kecemasan di masyarakat.